2005
DOI: 10.1152/jn.00836.2004
|View full text |Cite
|
Sign up to set email alerts
|

Light-Directed Electrical Stimulation of Neurons Cultured on Silicon Wafers

Abstract: . Lightdirected electrical stimulation of neurons cultured on silicon wafers. J Neurophysiol 93: 1090 -1098, 2005. First published September 22, 2004 doi:10.1152/jn.00836.2004. Dissociated neurons cultured in vitro can serve as a model system for studying the dynamics of neural networks. Such studies depend on techniques for stimulating patterns of neural activity. We show a technique for extracellular stimulation of dissociated neurons cultured on silicon wafers. When the silicon surface is reverse biased, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 34 publications
0
35
0
Order By: Relevance
“…A similar photoconductive stimulation scheme, using single crystal silicon as a photoconducting substrate, was adopted by Starovoytov et al 94 and is illustrated in Figure 1B. Here, stimulation is achieved by holding a fixed voltage between the p-type silicon and an Ag/AgCl counter electrode and modulating the laser beam illumination.…”
mentioning
confidence: 99%
“…A similar photoconductive stimulation scheme, using single crystal silicon as a photoconducting substrate, was adopted by Starovoytov et al 94 and is illustrated in Figure 1B. Here, stimulation is achieved by holding a fixed voltage between the p-type silicon and an Ag/AgCl counter electrode and modulating the laser beam illumination.…”
mentioning
confidence: 99%
“…In addition, some other unconventional applications of OEK technology have also been reported. For example, Starovoytov et al presented the possibility of light addressable electrical stimulation of cultured neurons with a similar structure to OEK device by replacing the transparent ITO electrode with a floating one [119,120]. Suzurikawa et al [34] reported the production of microscale pH gradient in OEK chips.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison to other optical methods for stimulating neurons in culture such as glutamate uncaging (Pettit et al, 1997) and optically stimulating neurons grown on silicon wafers (Colicos et al, 2001;Starovoytov et al, 2005), ChR2 fulfills the requirement for reversible, high-speed, spatiotemporal activation of select neuronal populations (Boyden et al, 2005). Repeated trials of single photon photolysis of caged glutamate could release large amounts of glutamate which might lead to toxicity or non-specific stimulation (Callaway and Katz, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Optically stimulating neurons grown on silicon wafers (Colicos et al, 2001;Starovoytov et al, 2005) was another promising method of non-invasive stimulation, but reliably eliciting action potentials meant increasing illumination intensity, which reduced spatial resolution. Additionally, the neurons could only be stimulated to fire action potentials after 3 weeks in vitro (Starovoytov et al, 2005).…”
Section: Discussionmentioning
confidence: 99%